Awareness of Stroke Warning Symptoms, Risk Factors, and Response to Acute Stroke in Biswanath District, Assam, India. Issue 2 (December 2020) - Kurmi, Sima; Mathews, Elezebeth; Kodali, Prakash Babu; Thankappan, K. R.
Introduction: This study was undertaken with the following objectives: (a) to find out the awareness of warning symptoms and risk factors of stroke, (b) response to acute stroke, and (c) factors associated with awareness, risk factors, and response to acute stroke among community-dwelling adults in Biswanath district of Assam. Methods: Using a cross-sectional design, a community-based study was done among 340 adults (mean age 38 years, men 55%) selected using multistage cluster sampling. Information on sociodemographic variables, stroke warning symptoms, risk factors, and response to acute stroke was collected using an adapted World Health Organization (WHO) STEPs stroke surveillance tool. Bivariate and logistic regression analysis were done to find out the factors associated with stroke warning symptoms, risk factors, and response to acute stroke. A " P " value < .05 was considered for statistical significance. Results: Awareness of stroke was significantly higher among males ( P < .01), better educated ( P < .01), government employees ( P < .05), high-income group ( P < .01), and those who reported receiving information from a professional source ( P < .01) compared to their counterparts. Knowledge of at least one stroke risk factor and providing at least one correct response to acute stroke was higher among males, better educated, government employees, higher income groups, and those who received information from professional source compared to their counterparts ( P < .05). Conclusion: Awareness of stroke warning symptoms, risk factors, and response to acute stroke needs to be improved focusing on women, low education groups, those working in the nongovernment sector, and low-income groups by health professionals.